Evaluating different physician's prescribing preference based instrumental variables in two primary care databases: a study of inhaled long‐acting beta2‐agonist use and the risk of myocardial infarction†. (March 2016) - Uddin, Md. Jamal; Groenwold, Rolf H. H.; de Boer, Anthonius; Afonso, Ana S. M.; Primatesta, Paola; Becker, Claudia; Belitser, Svetlana V.; Hoes, Arno W.; Roes, Kit C. B.; Klungel, Olaf H.
Abstract: Purpose: Instrumental variable (IV) analysis with physician's prescribing preference (PPP) as IV is increasingly used in pharmacoepidemiology. However, it is unclear whether this IV performs consistently across databases. We aimed to evaluate the validity of different PPPs in a study of inhaled long‐acting beta2‐agonist (LABA) use and myocardial infarction (MI). Methods: Information on adults with asthma and/or COPD and at least one prescription of beta2‐agonist, or muscarinic antagonist was extracted from the CPRD (UK) and the Mondriaan (Netherlands) databases. LABA exposure was considered time‐fixed or time‐varying. We measured PPPs using previous LABA prescriptions of physicians or proportion of LABA prescriptions per practice. Correlation (r) and standardized difference (SDif) were used to assess assumption of IV analysis. Results: For time‐fixed LABA, the IV based on 10 previous prescriptions outperformed the other IVs regarding strength of the IV (r ≥ 0.15) and balance of confounders between IV categories (SDif < 0.10). None of the IVs we considered appeared to be valid for time‐varying LABA. In CPRD (n = 490 499), which included approximately 18 times more subjects than Mondriaan (n = 27 459), IVs appeared more valid. LABA was not associated with MI; hazard ratios ranged from 0.86 to 1.18 for conventional analysis, and from 0.61 to 1.24 for the IV analyses with apparent valid IVs. Conclusions: The validity of physician's prescribing preference as IV strongly depends on how this IV is defined and in which database it is applied. Hence, general recommendations cannot be made, other than to generate several plausible IVs, assess their validity, and report the estimate(s) from apparently valid IVs. Copyright © 2016 John Wiley & Sons, Ltd.